Anna and the King of Siam [videorecording (DVD)] - Cromwell, John, 1886-1979; Dunne, Irene, 1898-1990; Harrison, Rex; Darnell, Linda, 1923-1965; Landon, Margaret, 1903-1993 (20th Century Fox Home Entertainment, 2005)
Anna and her son travel to the exotic kingdom of Siam to educate the harem and children of the king.